If it's not what You are looking for type in the equation solver your own equation and let us solve it.
1/4(28x-12)-(x+4)=0
Domain of the equation: 4(28x-12)!=0We get rid of parentheses
x∈R
1/4(28x-12)-x-4=0
We multiply all the terms by the denominator
-x*4(28x-12)-4*4(28x-12)+1=0
Wy multiply elements
-4x^2(2-16x(2+1=0
| 2x-5=1x-10 | | d-9=10-8d+8 | | 10d+8=6d+40 | | 1/p=2p-4 | | 1/4h+3/4+1/2h+2=5 | | 21g=945 | | 5/8p+4=3/8p+12 | | -2n+3+4n=5+5n-2= | | 6h-9=-9+h | | 2(-6x+4)=5x+2 | | X^2+(5x)^2=52^2 | | -8+u=-3u | | 2x+5+4x+3=180 | | 2/6=9n/5 | | Y+13=17;y=4 | | 2(3x-4)+1=5x+4 | | -7x+3=176 | | t-2÷3=1-t^2÷2 | | 6x²-10x=4x | | -x(x-3)+1=4x-1 | | 15=-1/4m-7 | | 3x+2x+x+10=100 | | t-2/3=1-t^2/2 | | 5x81=14x | | 0.8x=2.5 | | 7x=14;x=3 | | 5x82=14x | | ,2+z=4+10 | | 32=-4(v-5) | | 3x+7=x+49 | | 6.5n=-75 | | -y/3=-45 |